Correlation between blood international normalised ratio (INR) value and saliva prothrombin concentration in patients under warfarin therapy: An observational analytics study - Pratama, Rachendra; Sjamsudin, Endang; Tasman Yuza, Abel; Wijaya, Indra; Arief Ichwan, Solachuddin Jauhari (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2024)
Introduction: Oromaxillofacial surgery has a bleeding risk complication. Increasing bleeding risk can be caused by the use of blood clotting inhibitors, including warfarin. Warfarin is an anticoagulant that works by inhibiting coagulation factors in the cascade. International normalised ratio (INR) indicates warfarin monitoring and bleeding risk during surgical procedures. INR examination currently uses blood plasma. This research analyses the correlation between blood INR value and salivary prothrombin concentration. Methods: This research was an analytical observational with a correlational design on 19 samples examined using a human prothrombin reagent from Elabscience. The samples used were blood and saliva, and then ELISA tests were carried out on them. Data results were analysed with linear regression and correlation tests. Results: In this study, 19 samples were collected from 6 male and 13 female subjects. The average value of salivary prothrombin concentration in this study was 227.63 (ng/ml), and the blood INR value was 1.85. The normality test result showed that the data distribution was normal; therefore, the correlation and simple linear regression tests can be conducted. The correlation and regression tests showed a positive correlation between blood INR value and salivary prothrombin concentration with a correlation coefficient of r = 0.81 (p < 0.001). Conclusion: There is a positive relationship between blood INR value and salivary prothrombin concentration in oromaxillofacial patients under warfarin therapy.